Crossing body shadow (Malta : Universiti of Valetta, 1997)
Crossing body shadow may be the best described as an ecology of identity, mortality, and acting. The work gathered around investigations of internal and external corporeal modalities and explored their reverberations on and within disciplines of'performance'
Title from title screen
DVD format
Keywords: Theater